Substrate metabolism in male astronauts onboard the International Space Station: the ENERGY study - Elisa Le Roux; Alexandre Zahariev; Isabelle Chery; Dale A. Schoeller; Pierre Bourdier; Alain Maillet; Cecile Thevenot; Maël Garnotel; Guillemette Gauquelin-Koch; Laurie Van Den Berghe; Stéphane Blanc; Chantal Simon; et al. (npj Microgravity, 2024)
Abstract Bedrest shifts fasting and postprandial fuel selection towards carbohydrate use over lipids, potentially affecting astronauts’ performance and health. We investigated whether this change occurs in astronauts after at least 3 months onboard the International Space Station (ISS). We further explored the associations with diet, physical activity (PA), and body composition. Before and during spaceflight, respiratory quotient (RQ), carbohydrate, and fat oxidation were measured by indirect calorimetry before and following a standardized meal in 11 males (age = 45.7 [SD 7.7] years, BMI = 24.3 [2.1] kg m−²). Postprandial substrate use was determined by 0-to-260 min postprandial incremental area under the curve (iAUC) of nutrient oxidation and the difference between maximal postprandial and fasting RQ (ΔRQ). Food quotient (FQ) was calculated from diet logs. Fat (FM) and fat-free mass (FFM) were measured by hydrometry and PA by accelerometry and diary logs. Spaceflight increased fasting RQ (P = 0.01) and carbohydrate oxidation (P = 0.04) and decreased fasting lipid oxidation (P < 0.01). An increase in FQ (P < 0.001) indicated dietary modifications onboard the ISS. Spaceflight-induced RQ changes adjusted for ground RQ correlated with inflight FQ (P < 0.01). In postprandial conditions, nutrient oxidation and ΔRQ were unaffected on average. Lipid oxidation changes negatively correlated with FFM changes and inflight aerobic exercise and positively with FM changes. The opposite was observed for carbohydrate oxidation. ΔRQ changes were negatively and positively related to FM and FFM changes, respectively. In conclusion, fasting substrate oxidation shift observed during spaceflight may primarily result from dietary modifications. Between-astronaut variability in postprandial substrate oxidation depends on body composition changes and inflight PA.